Pengaruh Inokulasi Rhizobium sp. dan Pupuk Kandang Kambing terhadap Pertumbuhan dan Hasil Edamame pada Tanah Gambut - Prayonas, Walan; Zulfita, Dwi; Pramulya, Muhammad (Fakultas Pertanian, Universitas Tanjungpura, 2025)
Edamame (Glycine max L. Merill) is a legume native to Japan that thrives in tropical regions. West Kalimantan has significant potential for edamame cultivation due to its extensive peatlands. However, peat soils have limited nutrient availability and a high C/N ratio, making nitrogen less accessible to plants. To address this issue, Rhizobium sp. inoculation can enhance nitrogen availability, while goat manure improves soil properties. This study aims to determine the optimal combination of Rhizobium sp. inoculation and goat manure application for edamame growth and yield on peat soil. The experiment was conducted in Pontianak Tenggara from August 1 to October 6, 2024, using a factorial Completely Randomized Design (CRD) with two treatment factors. The first factor was the legin dose (L) at three levels: l1 = 2.5 g/kg, l2 = 5.0 g/kg, and l3 = 7.5 g/kg of edamame seeds. The second factor was the goat manure dose (K) at three levels: k1 = 5 tons/ha, k2 = 10 tons/ha, and k3 = 15 tons/ha, resulting in nine treatment combinations. The results showed that Rhizobium sp. inoculation at 7.5 g/kg of edamame seeds and goat manure application at 15 tons/ha provided the best outcomes for growth and productivity.